PATTANI DARUSALAM TRACE OF GLORY (A FORGOTTEN CIVILIZATION IN THE LAND OF SIAM) - Hasti Sulaiman (SOSIOEDUKASI, 2025)
ABSTRACT The purpose of this research is to identify the main characteristics and characteristics of the Pattani Darussalam civilization during its heyday, the factors supporting its success, and the reasons why Pattani Darussalam's existence has been forgotten or marginalized in historiography and collective consciousness. This article employs library research as its research method. The results of the study show that the characteristics of Pattani civilization include: a), the peaceful and inclusive spread of Islam, Islam did not come through conquest, but through trade and scholars from India, Arabia and the archipelago, b), Sharia-based government with matrilineal elements, unique in its heyday led by queens, reflecting the Malay matrilineal tradition that persisted despite patriarchal Islam, c), diverse culture and arts, artistic styles include mosque architecture with Malay-Islamic authority, such as the Krue Se Mosque, as well as crafts such as songket cloth, salted fish, and Muslim clothing and d), Maritime and international trade: Pattani is strategically located on the Malay Peninsula, making it a center of trade between the East (China, Japan) and the West (India, Arabia, Europe). Pattani Port developed as an important entrepot. The characteristics of Pattani Darussalam are The main characteristics of the Pattani kingdom during its glory days were the role of the Ulama and the civilization of knowledge, socio-culture, politics and diplomacy, economy and trade as well as military and defense. While the factors were the factors of conquest and domination of Siam, the factors of assimilation policy and cultural oppression by Siam, conflict and rebellion factors, economic and geographical factors as well as limitations in communication and historical writing.